Emotional Intelligence and Job Stress: In Its Influence on Teachers’ Performance - Bastian, Adolf; Wahyuni, Sri; Liza , Ledya Oktavia; Kasriyati, Destina; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
The competency test results for state high school teachers who served in Rokan Hilir Regency only passed 42 percent of the total teachers. This indicates that teachers’ performance is still poor. Internal and external factors both influence teachers’ performance. The internal factor is emotional intelligence, which is the ability to recognize one's own and other people's emotions. The external factor is job stress caused by the demands of the job and the work environment. The study aims to determine the impact of teachers’ emotional intelligence and job stress on teachers’ performance. This type of research uses a quantitative approach using linear regression analysis techniques. This research was conducted in all public high schools in the Rokan Hilir district. The population of this study was all teachers at public high schools who served in Rokan Hilir Regency, namely 879 teachers. Sampling using a random sampling technique with a size of 10% of the population, namely 90 teachers. The data collection technique is a non-test psychological measurement scale. Based on data analysis, the following results were obtained: Emotional intelligence has a significant influence on teachers’ performance at public high schools in Rokan Hilir Regency; Job stress has no significant effect on teachers’ performance at the State Senior High School of Rokan Hilir Regency; Job stress and emotional intelligence simultaneously have a significant impact on teachers’ performance.